Oxidation performance of plant oil as hydraulic fluid / W.B. Wan Nik ...[et al.] - Wan Nik, W.B; Ghazali, Z.; Ku Bulat, K.H; Senin, H.B; Rahman, M.M (2006)
Although petroleum based oils have been traditionally the most commonly used hydraulic fluid in the fluid power industry, they are being subjected to ever increasing controls particularly due to the increasingly stringent government regulations regarding their use. In response to the stringent controls, non-petroleum based fluid should be used. In this study an experimental evaluation of palm oil as alternative hydraulic fluid has been performed. The effect of additives towards the oxidative and thermal stability of palm oil was evaluated. Two types of commercial additives which are Irgalube F10 and Irganox L135 with different percentages were used during the experiment. Analysis conducted proved that addition of additives which act as antioxidant play an important role in improving thermal and oxidative stability of the palm oil.